2021
DOI: 10.3390/jcm10112533
|View full text |Cite
|
Sign up to set email alerts
|

The New Status of Parasitic Diseases in the COVID-19 Pandemic—Risk Factors or Protective Agents?

Abstract: It is possible that parasites may influence the course of COVID-19 infection, as either risk factors or protective agents; as such, the current coronavirus pandemic may affect the diagnosis and prevention of parasitic disease, and its elimination programs. The present review highlights the similarity between the symptoms of human parasitoses and those of COVID-19 and discuss their mutual influence. The study evaluated selected human parasitoses with similar symptoms to COVID-19 and examined their potential inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 75 publications
0
24
0
2
Order By: Relevance
“…Wolday et al ( 2021 ) reported that the patients co-infected with parasites had lower odds of developing severe COVID-19. It has been hypothesized that the low incidence rates of COVID-19 could result from increased exposure to parasites in some countries (Głuchowska et al 2021 ). It has also been proposed that parasites may cause a better tolerance of COVID-19 (Ssebambulidde et al 2020 ; Fonte et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wolday et al ( 2021 ) reported that the patients co-infected with parasites had lower odds of developing severe COVID-19. It has been hypothesized that the low incidence rates of COVID-19 could result from increased exposure to parasites in some countries (Głuchowska et al 2021 ). It has also been proposed that parasites may cause a better tolerance of COVID-19 (Ssebambulidde et al 2020 ; Fonte et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…International Journal of Infectious Diseases During the overheating investigations of factors that can decrease COVID-19 severity, coinfection with some parasitic diseases was identified ( Gluchowska et al, 2021 ). In this letter, we will elaborate why we think that the protective effect of intestinal parasitic coinfection with COVID-19 could be a myth.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 96%
“…The Covid-19 pandemic has marginalized many other illnesses because of interruptions (Gluchowska, et al,2021;Hotez, et al, 2021). Before the pandemic, the World Health Organization (WHO) classified several infectious diseases as neglected tropical diseases (NTD) (World Health Organization & United Nations Children's Fund, 2020).…”
Section: Introductionmentioning
confidence: 99%